Analysis on Short Podcast and Critical Thinking Skills-Infused in Speaking Learning Materials (Universitas PGRI Sumatera Barat, 2023)
Every person in this global era must be well ready to confront the most recent innovations. There continue to be numerous seventh-graders who struggle to communicate in English. As of now, their issues have included shyness, lack of confidence, monotonous materials, a lack of digital utilization, and a variety of others. There has been much research in this field, but this is the most recent report that incorporates short podcast, Kurikulum Merdeka Belajar, and critical thinking skills. In this circumstance, the study will examine existing speaking learning material that incorporates 21st century skills, such as short podcasts and critical thinking skills. It was thought that a short podcast and critical thinking ability could spark students' interest in speaking. This is a qualitative study. The English learning materials were gathered in order to determine whether or not short podcasts and critical thinking skills were infused. Teachers from four different schools in Depok, Bekasi, and Bogor were also interviewed. According to the study's findings, critical thinking has been infused but not yet sufficiently for students' speaking skills, and short podcasts have not been infused due to a variety of reasons. This investigation will be continued with additional research.